Quantifying the effectiveness of interventions for people with common health conditions in enabling them to stay in or return to work: a rapid evidence assessment - Dibben, Pauline; Wood, Geoffrey; Nicolson, Rod; O'Hara, Rachel (London, 2012)
"This rapid evidence assessment examined evidence available on the effectiveness of health and work interventions to help people with common health conditions to stay in work or return to work. The evidence assessment was commissioned to inform policy development on how to sustain employment for those with common physical and mental health conditions, and the perceived lack of clear evidence on employment outcomes. Building on previous evidence reviews, the objective was to understand the quantitative impact of such interventions, considering the latest available evidence (2008-2011)."